Framing Biblical Inclusive Theology in Acts 10:12-16, 34-36 - Sitio, Robert Juni Tua; Limbong, Nurelni; Siburian, Bernhardt; Simanjuntak, Ririn; Lumbantobing, Grace Na Anantha (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
This article offers a biblical theological for Christians to act inclusively toward other faiths. This biblical inclusive theology frame is a guideline for the church to be used as a consideration in conducting inter-religious and cultural encounters and dialogues. This study used hermeneutical approach on Acts 10:12-16, 34-36. The method used in this study is descriptive qualitative which aims to understand and describe real events based on facts. In the context of this research, the data analyzed is a discourse obtained from relevant data sources. The result of this study showed that inclusivity does not eliminate the belief in the exclusivity of Christ as saviour, but rather the acceptance of different people as part of Christian people.